A highly hydrophobic oil-water separation material, and its preparation method and application

By growing ZIF-8 in situ on melamine foam and exchanging shells, D-ZIF-8/MF highly hydrophobic oil-water separation material was prepared, which solved the safety hazards and secondary pollution problems of using strong oxidants in the prior art, and achieved efficient, safe and low-cost oil-water separation effect.

CN115591276BActive Publication Date: 2025-03-25SICHUAN NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211184116.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-27
Publication Date
2025-03-25
Estimated Expiration
2042-09-27

AI Technical Summary

Technical Problem

The existing oil-water separation materials use strong oxidants with high safety hazards and difficult waste liquid treatment during the pretreatment process, and there is a risk of secondary pollution, making it difficult to achieve low-cost, safe and efficient oil-water separation.

Method used

By pretreating the melamine foam, ZIF-8 is grown in situ using a mixed solution of zinc nitrate hexahydrate and dimethylimidazole, followed by shell exchange to enhance the hydrophobicity of the material, and D-ZIF-8/MF highly hydrophobic oil-water separation material was prepared.

Benefits of technology

It achieves efficient oil-water separation effect, and the material has excellent stability, corrosion resistance, and recyclability, and does not produce secondary pollution. It is suitable for the treatment of oil-water pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115591276B_ABST
    Figure CN115591276B_ABST
Patent Text Reader

Abstract

The present invention discloses a highly hydrophobic oil-water separation material, a preparation method and an application thereof, and relates to a highly hydrophobic oil-water separation material. The preparation method includes pretreatment, in-situ growth and shell exchange. The highly hydrophobic oil-water separation material is applied in water pollution treatment. Shell exchange after in-situ growth of ZIF‑8 of the present invention does not change the surface morphology structure of nanoparticles on the skeleton. The prepared D‑ZIF‑8 / MF is more hydrophobic than the original ZIF‑8 / MF, and the contact angle increases from 123.2° to 145.1°. D‑ZIF‑8 / MF can absorb up to 68‑165 times of its own weight of oil / organic solvent, and has excellent stability, corrosion resistance, recyclability, no secondary pollution, and has good application prospects in treating oil and water pollution.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a highly hydrophobic oil-water separation material, and in particular to a highly hydrophobic oil-water separation material, and a preparation method and application thereof. Background Art

[0002] Pollution caused by oil spills is a serious problem. Oil spills are difficult to clean up, and the recovery of oil can cause huge economic losses and long-term environmental impacts. With the continued development of the economy, oil spills will always be inevitable in the future. Traditional technologies (gravity separation, centrifugation, flotation and biodegradation) have been widely studied for separating oil-water mixtures, but these technologies have low separation efficiency, high cost, and are prone to secondary pollution if not handled properly. Achieving oil-water separation without causing secondary pollution is a challenging task, and the materials for oil-water separation are crucial.

[0003] At present, a large amount of high adsorption capacity and good oil-water separation materials with good recycling performance have been studied, but the existing oil-water separation materials use normal hexane or toluene reagents as reaction solvents, and the pretreatment process uses strong acid reagents, etc., which has potential safety hazards, and the waste liquid is not easy to handle after the adsorption treatment, and secondary pollution is caused again. For example, Chinese patent CN110684234A discloses a simple, low-cost ultralight, super-hydrophobic sponge preparation method, which is prepared by a strong oxidant with a modified super-hydrophobic super-oleophilic sponge, although the hydrophobic and oleophilic sponge prepared by the method has good mechanical properties and cyclic adsorption capacity, it can keep its original appearance and adsorption performance after repeated extrusion and recycling. However, the method uses strong oxidizing materials such as hydrogen peroxide, potassium persulfate, potassium ferrate, etc., which has potential safety hazards and is not conducive to the processing of waste liquid. Therefore, it is urgent to prepare an oil-water separation material with low production cost, high safety, easy operation, no secondary pollution, and good oil-water separation effect. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a highly hydrophobic oil-water separation material, and a preparation method and application thereof.

[0005] The object of the present invention is achieved by the following technical scheme: a method for preparing a highly hydrophobic oil-water separation material, which comprises the following steps:

[0006] S1. Pretreatment: soak the melamine foam in methanol and ethanol for 25 to 35 minutes respectively and then dry it;

[0007] S2. In situ growth: the pretreated melamine foam was placed in a mixed solution of zinc nitrate hexahydrate and dimethylimidazole and allowed to grow for 10 to 14 hours, and ZIF-8 / MF was obtained after drying;

[0008] S3. Shell exchange: ZIF-8 / MF was immersed in a mixed solution of 5,6-dimethylbenzimidazole, triethylamine and methanol, and heated with stirring at 55-65°C for 13-18h to perform shell exchange, thereby obtaining D-ZIF-8 / MF highly hydrophobic oil-water separation material.

[0009] Furthermore, the size of the melamine foam is 1cm*1cm*1cm.

[0010] Furthermore, the molar concentration ratio of zinc nitrate hexahydrate to dimethylimidazole in the mixed solution in step S2 is 1:1.5-3.

[0011] Furthermore, the molar concentration ratio of 5,6-dimethylbenzimidazole, triethylamine and methanol in the mixed solution in step S3 is 1:0.5-1.5:140-180.

[0012] Furthermore, the drying is vacuum drying, the drying temperature is 55-65° C., and the drying time is 5-7 hours.

[0013] The highly hydrophobic oil-water separation material is prepared by the above method.

[0014] Application of the highly hydrophobic oil-water separation material in water pollution treatment.

[0015] Furthermore, the water pollution treatment is to absorb the oil or organic solvent in the sewage.

[0016] The principle of the present invention is:

[0017] The high nitrogen content of melamine foam provides abundant possible binding sites for the growth of ZIF-8, making them a good combination with the ZIF-8 structure without any pre-modification. The surface structure of ZIF-8 on the melamine foam (MF) skeleton is controlled by adjusting the concentration of zinc nitrate hexahydrate and dimethylimidazole solution. The appropriate concentration ensures the uniform growth of ZIF-8 or the continuous growth of ZIF-8 film. The ZIF-8 film layer will not break under compression and bending and has high stability. This property allows ZIF-8 to stably bind to the MF skeleton surface without any adhesive.

[0018] Shell exchange, which can change the functional groups in the organic linker after the initial reaction while maintaining the same framework structure, can be used to enhance the hydrophobicity of ZIF-8. ZIF-8 nanoparticles were effectively functionalized via shell exchange reaction with 5,6-dimethylbenzimidazole (DMBIM).

[0019] The invention has the following advantages: the invention pre-treats melamine foam using non-toxic methanol and ethanol solutions, then in-situ grows ZIF-8 on a melamine foam skeleton, enhances the hydrophobicity of ZIF-8 by shell exchange, and prepares a super-hydrophobic coating by a bonding method in the prior art. The key step of the bonding method is the construction of a layered micro-nano structure, but it is difficult to control the surface morphology of the hydrophobic layer prepared by the bonding method. The invention in-situ grows ZIF-8 and then performs shell exchange without changing the surface morphology structure of nanoparticles on the skeleton. The prepared D-ZIF-8 / MF is more hydrophobic than the original ZIF-8 / MF, and the contact angle increases from 123.2° to 145.1°. The D-ZIF-8 / MF can absorb oil / organic solvents up to 68-165 times of its own weight, and has excellent stability, corrosion resistance, recyclability, no secondary pollution, and has good application prospects in treating oil and water pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the preparation of D-ZIF-8 / MF according to the present invention.

[0021] Figure 2 It is the absorption capacity of D-ZIF-8 / MF for various oils and organic solvents.

[0022] Figure 3 The effect of NaCl concentration on the water contact angle of D-ZIF-8 / MF.

[0023] Figure 4 The effect of pH on the water contact angle of D-ZIF-8 / MF.

[0024] Figure 5 This is the chemical stability test chart of D-ZIF-8 / MF.

[0025] Figure 6 This is the cyclic test graph of D-ZIF-8 / MF absorbing organic solvents and the water contact angle change graph.

[0026] Figure 7 This is the thermogravimetric analysis test graph of D-ZIF-8 / MF and the water contact angle after high-temperature sintering at 200℃ for 2h.

[0027] Figure 8 This is the compression stress-strain curve test diagram of D-ZIF-8 / MF. DETAILED DESCRIPTION

[0028] The present invention is further described below in conjunction with the accompanying drawings and embodiments. The protection scope of the present invention is not limited to the following: Example 1: A method for preparing a highly hydrophobic oil-water separation material, which comprises the following steps:

[0029] S1. Pretreatment: Take melamine foam, cut into a size of 1cm*1cm*1cm, soak it in methanol and ethanol for 35min each under ultrasonic conditions, repeat three times, take it out and dry it in a vacuum oven at 55℃ for 5h;

[0030] S2. In situ growth: the pretreated melamine foam was placed in a mixed solution of zinc nitrate hexahydrate and dimethylimidazole and allowed to grow for 10 hours, and then dried at 55°C for 5 hours to obtain ZIF-8 / MF; wherein the molar concentration ratio of zinc nitrate hexahydrate to dimethylimidazole in the mixed solution was 1:1.5;

[0031] S3. Shell exchange: ZIF-8 / MF was immersed in a mixed solution of 5,6-dimethylbenzimidazole, triethylamine and methanol, wherein the molar concentration ratio of 5,6-dimethylbenzimidazole, triethylamine and methanol was 1:0.5:140, and the mixture was stirred and heated at 55°C for 13 h to perform shell exchange, thereby obtaining D-ZIF-8 / MF highly hydrophobic oil-water separation material.

[0032] Embodiment 2: A method for preparing a highly hydrophobic oil-water separation material, comprising the following steps:

[0033] S1. Pretreatment: Take melamine foam, cut into a size of 1cm*1cm*1cm, soak it in methanol and ethanol for 25min each under ultrasonic conditions, repeat three times, take it out and dry it in a vacuum oven at 65℃ for 7h;

[0034] S2. In situ growth: the pretreated melamine foam was placed in a mixed solution of zinc nitrate hexahydrate and dimethylimidazole and allowed to grow for 14 hours, and then dried at 65°C for 7 hours to obtain ZIF-8 / MF; wherein the molar concentration ratio of zinc nitrate hexahydrate to dimethylimidazole in the mixed solution was 1:3;

[0035] S3. Shell exchange: ZIF-8 / MF was immersed in a mixed solution of 5,6-dimethylbenzimidazole, triethylamine and methanol, wherein the molar concentration ratio of 5,6-dimethylbenzimidazole, triethylamine and methanol was 1:1.5:180, and the mixture was stirred and heated at 65°C for 18 h to perform shell exchange, thereby obtaining D-ZIF-8 / MF highly hydrophobic oil-water separation material.

[0036] Embodiment 3: A method for preparing a highly hydrophobic oil-water separation material, comprising the following steps:

[0037] S1. Pretreatment: Take melamine foam, cut into a size of 1cm*1cm*1cm, soak it in methanol and ethanol for 30min each under ultrasonic conditions, repeat three times, take it out and dry it in a vacuum oven at 60℃ for 6h;

[0038] S2. In situ growth: the pretreated melamine foam was placed in a mixed solution of zinc nitrate hexahydrate and dimethylimidazole and allowed to grow for 12 hours, and dried at 60°C for 6 hours to obtain ZIF-8 / MF; wherein the molar concentration ratio of zinc nitrate hexahydrate to dimethylimidazole in the mixed solution was 1:2;

[0039] S3. Shell exchange: ZIF-8 / MF was immersed in a mixed solution of 5,6-dimethylbenzimidazole, triethylamine and methanol, wherein the molar concentration ratio of 5,6-dimethylbenzimidazole, triethylamine and methanol was 1:0.7:160, and the mixture was stirred and heated at 60°C for 16 h to perform shell exchange, thereby obtaining D-ZIF-8 / MF highly hydrophobic oil-water separation material.

[0040] The beneficial effects of the present invention are described below by experiments:

[0041] (1) Preparation of D-ZIF-8 / MF: Figure 1 shown.

[0042] a. Material pretreatment: Cut melamine foam (1cm*1cm*1cm) and pretreat it with methanol or ethanol.

[0043] b. In situ growth of ZIF-8: 10 mL of zinc nitrate hexahydrate and dimethylimidazole solution with a molar concentration ratio of 1:2 were prepared respectively, where the concentration of dimethylimidazole was 75 mmol / L. After the two solutions were mixed, ZIF-8 / MF was put into the mixed solution for static growth for 12 h, and then dried in an oven to obtain ZIF-8 / MF.

[0044] c. Shell exchange: A piece of ZIF-8 / MF was immersed in a solution of 5,6-dimethylbenzimidazole, triethylamine and methanol in a molar ratio of 1:0.7:160, heated with stirring at 60°C for 15h, and dried in an oven to obtain D-ZIF-8 / MF.

[0045] (2) D-ZIF-8 / MF:

[0046] a. Absorption capacity of D-ZIF-8 / MF: Weigh D-ZIF-8 / MF and immerse it in various oils and organic solvents: cyclohexane (CYH), monobromomethane (MB), ethylene dichloride (EDC), dimethyl ether (DME), peanut oil (Peanut oil), petroleum ether (PE), trichloromethane (MSDS), diesel, tetrachloroethylene (PERC), and n-hexane (n-hexane) for 5 minutes. Then, take out the foam until the residual surface solvent drips off and weigh it quickly.

[0047] b. D-ZIF-8 / MF performance test: test the corrosion resistance, high temperature resistance, compressive stress-strain, recyclability, etc. of D-ZIF-8 / MF.

[0048] Experiment 1

[0049] D-ZIF-8 / MF was weighed (M0) and immersed in various oils and organic solvents for 5 min. Then, the foam was removed until the residual surface solvent dripped off and quickly weighed (M1). The absorption capacity of D-ZIF-8 / MF for various oils and organic solvents was tested using formula (1).

[0050]

[0051] Where M0(g) and M1(g) are the weights of the foam before and after absorption. The absorption capacity of various oils and organic solvents is as follows: Figure 2 The results showed that D-ZIF-8 / MF could absorb oil / organic solvent up to 68-165 times its own weight.

[0052] Experiment 2

[0053] Prepare 100 mL of 5mmol / L, 50mmol / L, 100mmol / L, 300mmol / L, and 600mmol / L NaCl solutions. Under the action of external force, soak D-ZIF-8 / MF in NaCl solutions of different concentrations for 24 hours, take out and dry, and measure the contact angle. Figure 3 The results showed that NaCl concentration had little effect on the hydrophobicity of D-ZIF-8 / MF. Even after immersion in a high concentration of 600 mmol / L NaCl solution, the WCA remained at 142°.

[0054] Experiment 3

[0055] Aqueous solutions with pH values ​​of 2, 3, 6, 7, 9, 11, and 13 were prepared, and water droplets with pH values ​​of 2, 3, 6, 7, 9, 11, and 13 were dropped onto the surface of D-ZIF-8 / MF. The contact angles were measured as follows: Figure 4 The results showed that the WCA of D-ZIF-8 / MF was the highest under neutral conditions (pH = 7), and D-ZIF-8 / MF remained highly hydrophobic with increasing pH. The WCA of D-ZIF-8 / MF still reached 135° and 137° at pH 2 and 13, respectively.

[0056] Experiment 4

[0057] D-ZIF-8 / MF was immersed in different organic solvents for 24 h, taken out, washed with ethanol, and dried in an oven. The contact angle was measured as follows: Figure 5After D-ZIF-8 / MF was immersed in ethylene dichloride (EDC), cyclohexane (CYH), methylbenzene (MB), chloroform (MSDS), petroleum ether (PE), tetrachloroethylene (PERC), 2-methoxyethanol (DME) and n-hexane solution (n-hexane), the WCA decreased slightly, but still remained above 135°.

[0058] Experiment 5

[0059] In Experiment 1, the organic solvent in the foam that absorbs 1,2-dichloroethane was squeezed out first, and after repeated washing with ethanol, it was dried in an oven and the absorption capacity of WCA and 1,2-dichloroethane was tested. The above operation was repeated 20 times, and the WCA and absorption capacity were recorded each time. Figure 6 As shown in the figure, after 20 cycles of continuous adsorption and desorption, the absorption capacity of D-ZIF-8 / MF still remained at a high level, reaching 116 times, with only a decrease of 6.3%. The WCA of D-ZIF-8 / MF was still higher than 130° after 20 repetitions. These results show that D-ZIF-8 / MF has excellent absorption capacity, high stability and reusability, and shows great prospects in practical applications.

[0060] Experiment 6

[0061] Thermogravimetric analysis (TGA) of pristine MF and D-ZIF-8 / MF was performed, and WCA was tested after calcining pristine MF and D-ZIF-8 / MF at 200 °C for 2 h. Figure 7 , the weight loss efficiency of the original MF at 300 °C is about 10%, and the thermal stability is slightly improved after loading D-ZIF-8. After MF and D-ZIF-8 / MF are heated at 200 °C for 2 h, the WCA of MF is 0°, and the water on the surface of MF is immediately absorbed, while the WCA of D-ZIF-8 / MF remains at 140°.

[0062] Experiment 7

[0063] The mechanical properties of D-ZIF-8 / MF were evaluated by compressive stress-strain test and cyclic compression test. Figure 8 As shown in Figure 2, the stress-strain curves show that D-ZIF-8 / MF can be compressed to a larger strain (80%) at a relatively low stress (32.5 kPa) due to its high porosity and elasticity ( Figure 8 a). D-ZIF-8 / MF underwent slight plastic deformation of less than 10% of the original value after the first and second compression cycles ( Figure 8 b). After that, as the cycle progresses, the stress-strain curve remains almost unchanged ( Figure 8 c). The WCA of D-ZIF-8 / MF remains above 143.1° after seven cycles.

[0064] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which are all covered by the protection scope of the present invention.

Claims

1. A method for preparing a highly hydrophobic oil-water separation material, characterized in that: It includes the following steps: S1. Pretreatment: Take melamine foam, soak it in methanol and ethanol for 25 to 35 minutes respectively, and then dry it; S2. In situ growth: The pretreated melamine foam was placed in a mixed solution of zinc nitrate hexahydrate and dimethylimidazole and allowed to grow for 10 to 14 hours, and then dried to obtain ZIF-8 / MF; S3. Shell exchange: ZIF-8 / MF was immersed in a mixed solution of 5,6-dimethylbenzimidazole, triethylamine and methanol, and heated with stirring at 55-65°C for 13-18h to perform shell exchange, thereby obtaining D-ZIF-8 / MF highly hydrophobic oil-water separation material.

2. The method for preparing a highly hydrophobic oil-water separation material according to claim 1, characterized in that: The size of the melamine foam is 1cm*1cm*1cm.

3. The method for preparing a highly hydrophobic oil-water separation material according to claim 1, characterized in that: The molar concentration ratio of zinc nitrate hexahydrate to dimethylimidazole in the mixed solution in step S2 is 1:1.5-3.

4. The method for preparing a highly hydrophobic oil-water separation material according to claim 1, characterized in that: The molar concentration ratio of 5,6-dimethylbenzimidazole, triethylamine and methanol in the mixed solution in step S3 is 1:0.5-1.5:140-180.

5. The method for preparing a highly hydrophobic oil-water separation material according to claim 1, characterized in that: The drying is vacuum drying, the drying temperature is 55-65° C., and the drying time is 5-7 hours.

6. A highly hydrophobic oil-water separation material prepared according to the method described in any one of claims 1 to 5.

7. Use of the highly hydrophobic oil-water separation material according to claim 6 in water pollution treatment.

8. The use according to claim 7, characterized in that: The water pollution treatment is to absorb the oil or organic solvent in the sewage.

Citation Information

Patent Citations

  • Simple and low-cost preparation method of super-hydrophobic sponge material

    CN110684234A

  • Aqueous composite zinc-aluminum anticorrosion coating

    CN107964351A

  • Melamine@ZIF-67 modified sponge oil absorption material as well as preparation method thereof

    CN109046279A